Microbial gene expression during hibernation in arctic ground squirrels: greater differences across gut sections than in response to pre-hibernation dietary protein content - Grond, Kirsten; Buck, C. Loren; Duddleston, Khrystyne N. (Frontiers in Genetics, 2023)
Obligate seasonal hibernators fast for 5 to 9 months depending on species yet resist muscle atrophy and emerge with little lean mass loss. The role of the gut microbiome in host nitrogen metabolism during hibernation is therefore of considerable interest, and recent studies support a role for urea nitrogen salvage (UNS) in host-protein conservation. We were interested in the effect of pre-hibernation diet on UNS and the microbial provision of essential amino acids (EAAs) during hibernation; therefore, we conducted a study whereby we fed arctic ground squirrels (Urocitellus parryii) pre-hibernation diets containing 9% vs 18% protein and compared the expression of gut bacterial urease and amino acid (AA) metabolism genes in 4 gut sections (cecum mucosa, cecum lumen, small intestine [SI] mucosa, and SI lumen) during hibernation. We found that pre-hibernation dietary protein content did not affect expression of complete bacterial AA pathway genes during hibernation; however, several individual genes within EAA pathways were differentially expressed in squirrels fed 18% pre-hibernation dietary protein. Expression of genes associated with AA pathways was highest in the SI and lowest in the cecum mucosa. Additionally, the SI was the dominant expression site of AA and urease genes and was distinct from other sections in its overall microbial functional and taxonomic composition. Urease expression in the gut microbiome of hibernating squirrels significantly differed by gut section, but not by pre-hibernation dietary protein content. We identified two individual genes that are part of the urea cycle and involved in arginine biosynthesis, which were significantly more highly expressed in the cecum lumen and SI mucosa of squirrels fed a pre-hibernation diet containing 18% protein. Six bacterial genera were responsible for 99% of urease gene expression: Cupriavidus., Burkholderia, Laribacter, Bradhyrizobium, Helicobacter, and Yersinia. Although we did not find a strong effect of pre-hibernation dietary protein content on urease or AA metabolism gene expression during hibernation, our data do suggest the potential for pre-hibernation diet to modulate gut microbiota function during hibernation, and further investigations are warranted.